HUBUNGAN KEPUASAN KERJA DENGAN PERILAKU CARING PERAWAT DI RUANG RAWAT INAP IRINA C RSUP. PROF. DR. R. D. KANDOU MANADO - Fabio Del Vigo Winokan; Ferlan Ansye Pondaag; Dina Mariana Larira (JURNAL KEPERAWATAN, 2022)
Background: Caring is a center in nursing practice because it requires that each nurse apply good performance in giving caring to patients in order to create quality service. Caring behavior is not always done by a nurse, one of which requires motivation in one’s nurse through work satisfaction. Purpose: to find out the working satisfaction of working with the patient behavior of Irina C RSUP Prof. Dr. R. D. Kandou Manado. Methods: this type of study is a quantitative study, using corvisiting study design with a sectional study approach. The sample consists of 63 executive nurse using a total sample sampling technique. The instruments use a work based questionnaire satisfaction based on the Maslow’s hierarchy of 16 statements and caring behavior questionnaire based on the carrative factors Watson developed Cronin & Horizon. Results: Research shows the satisfaction of a nurse’s work is in the high category and caring behavior in the good category. The statiscal test using spearman test at a trust rate of 95% or 0,05, obtained p value 0,002 and coefficiencies 0,401. Conclusion: there is a significant connection between work satisfaction and caring behavior in the hospital of Irina C RSUP Prof. Dr. R. D. Kandou Manado. What hospital management needs to do to maintain job satisfaction is to provide the motivation for carin’s behavior